Transient Early Fine Motor Abnormalities in Infants Born to COVID-19 Mothers Are Associated With Placental Hypoxia and Ischemia - Liu, Huan-Yu; Guo, Juanjuan; Zeng, Chang; Cao, Yuming; Ran, Ruoxi; Wu, Tiancheng; Yang, Guifang; Zhao, Dongchi; Yang, Pu; Yu, Xuechen; Zhang, Wei; Liu, Song-Mei; et al. (Frontiers in Pediatrics, 2022)
Background: Long-term effects of Coronavirus Disease 2019 (COVID-19) on infants born to infected mothers are not clear. Fine motor skills are crucial for the development of infant emotional regulation, learning ability and social skills. Methods: Clinical information of 100 infants born to 98 mothers (COVID-19 n=31, non-COVID-19 n=67) were collected. Infants were follow-up up to 9 months postpartum. The placental tissues were examined for SARS-CoV-2 infection, pathological changes, cytokines, and mtDNA content. Results: Decreased placental oxygen and nutrient transport capacity were found in infected pregnant women. Increased IL-2, IL-6, TNF-α and IFN-γ were detected in trophoblast cells and maternal blood of COVID-19 placentas. Elevated early fine motor abnormal-ities and increased serum TNI (troponin I) levels at delivery were observed in infants born to mothers with COVID-19. Increased abnormal mitochondria and elevated mtDNA content were found in the placentas from infected mothers. The placental mtDNA content of three infants with abnormal DDST were increased by 4%, 7% and 10%, respectively, compared to the mean of the COVID-19 group. The Maternal Vascular Malperfusion (MVM), elevated cytokines and increased placental mtDNA content in mothers with COVID-19 might be associated with transient early fine motor abnormalities in infants. These abnormalities are only temporary, and they could be corrected by daily training. Conclusions: Babies born to COVID-19 mothers with mild symptoms appeared to have little or no excess long-term risks of abnormal physical and neurobehavioral development as compared with the infants delivered by non-COVID-19 mothers.